ChemInform Abstract: Chemical Genetic Approaches for the Investigation of Neutral Lipid Metabolism. Issue 16 (March 2016) - Doler, Carina; Schweiger, Martina; Zimmermann, Robert; Breinbauer, Rolf
Abstract: Review: [184 refs.